2012
DOI: 10.1103/physrevb.86.245201
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport and quantum localization effects in organic semiconductors

Abstract: We explore the charge transport mechanism in organic semiconductors based on a model that accounts for the thermal intermolecular disorder at work in pure crystalline compounds, as well as extrinsic sources of disorder that are present in current experimental devices. Starting from the Kubo formula, we develop a theoretical framework that relates the time-dependent quantum dynamics of electrons to the frequency-dependent conductivity. The electron mobility is then calculated through a relaxation time approxima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
124
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(130 citation statements)
references
References 52 publications
6
124
0
Order By: Relevance
“…[52,62] have shown that at intermediate values of the ratio s/J, corresponding to the experimentally relevant temperature range, both extended "band-like" carriers and incoherent excitations coexist in different regions of the excitation spectrum: carriers with a markedly itinerant character are mostly located within the bulk of the band, while the most dramatic effects of inter-molecular fluctuations are instead concentrated around the band tails, where they cause the states to have a more localized character. The origin of the long-standing controversy on the microscopic identity of the charge carriers in organic semiconductors comes from the fact that different experimental probes will see alternatively one feature or the other, or a mixture of both.…”
Section: Reconciling the Band-like / Localized Carriers Dualitymentioning
confidence: 99%
See 3 more Smart Citations
“…[52,62] have shown that at intermediate values of the ratio s/J, corresponding to the experimentally relevant temperature range, both extended "band-like" carriers and incoherent excitations coexist in different regions of the excitation spectrum: carriers with a markedly itinerant character are mostly located within the bulk of the band, while the most dramatic effects of inter-molecular fluctuations are instead concentrated around the band tails, where they cause the states to have a more localized character. The origin of the long-standing controversy on the microscopic identity of the charge carriers in organic semiconductors comes from the fact that different experimental probes will see alternatively one feature or the other, or a mixture of both.…”
Section: Reconciling the Band-like / Localized Carriers Dualitymentioning
confidence: 99%
“…As was studied systematically both theoretically [52] and experimentally [25], extrinsic sources of disorder can affect carrier transport even in the purest samples available nowadays, especially when these are placed in FET geometries. Static disorder causes the mobility to degrade at low temperature in the best cases, and wash out the intrinsic transport regime completely in the worst cases, leading to a thermally activated behavior.…”
Section: Molecularmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to overcome this difficulty the fluctuations of the lattice vibrations, completely neglected in the adiabatic approximation (it becomes exact when ω 0 → 0 and the ionic mass M → ∞ keeping k = M ω 2 0 constant [17]), have to be taken into account. To this aim it has been proposed: i) to employ mixed quantum-classical simulations based on the Ehrenfest coupled equations [14]; ii) to neglect vertex corrections in the OC calculation [18]; iii) to introduce an ad hoc energy broadening of the system energy levels [15]. All these approximated approaches, although able to reproduce a power law dependence of mobility vs temperature, do not restore the conductivity values quantitatively.…”
mentioning
confidence: 99%